Field-Programmable Gate Arrays (FPGA) Adoption in Biofuelprocessing: The Role of Policy Incentives, Financial Mechanisms, and Strategic Management - Izhal Abdul Halin; Noreffendy Tamaldin; Mohd Effandi Yusoff; Jamal Abdul Nassir Shaari; Alias Abdullah; Irwan Ibrahim (RSIS International, 2026)
Indexed by ERA